FREQUENCY OF STATIN USE IN TYPE 2 DIABETICS HAVING MACROVASCULAR DISEASE- AT A TERTIARY CARE HOSPITAL OF KARACHI - Basit, Abdul; Hydrie, M. Zafar Iqbal; Hakeem, Rubina; Ahmedani, M. Yakoob; Masood, Qamar (Journal of Ayub Medical College Abbottabad, 2004)
Background: During the last two decades with the introduction of statins large reductions in cholesterol concentrations were easily and safely achievable and this led to studies that demonstrated benefits of statin use. But only fewer than one fourth of adults with coronary heart disease were receiving lipid-lowering drugs in a cross sectional health survey done in England. Thus this study was designed to evaluate the frequency of statin use in type 2 Pakistani diabetic subjects with macrovascular disease attending a tertiary care unit in Karachi, Pakistan. Methods: Records of type 2 diabetic subjects coming to the outpatient department of Baqai Institute of Diabetology and Endocrinology from September 1996 to December 2001 was analyzed for their anthropometric and biochemical characteristics. Patients having any macrovascular disease were identified and frequency of statin use by these subjects was studied. Results: Out of a total of 2152 patients 502 (252 males, 250 females) having macrovascular disease were identified. Only 16.5% of them (44 males, 39 females) were taking statins. Use of statins was higher amongst those who had angina (20%) or myocardial infarction (17%) compared to those who had stroke (10%). Sixty two percent of the users while 52% of the non-users had elevated blood cholesterol. Conclusion: Frequency of statin use in the subjects studied was much lower than was warranted with respect to their disease status. Presence of elevated blood cholesterol despite using statins suggested inappropriate treatment in these subjects. Further studies are required to identify the factors leading to low use of statins in type 2 diabetic subjects with macrovascular symptoms. Keywords: Statin Users, Frequency, Lipid profile, Type 2 Diabetes, Pakistan, Macrovascular, Angina, Myocardial Infarction, Stroke.